Obstacle to Learning Algebra in Elementary Schools - Eza Fauziah; Dindin Abdul Muiz Lidinillah; Ika Fitri Apriani (AlphaMath : Journal of Mathematics Education, 2023)
This research is based on the results of a preliminary study which identified students' learning barriers in algebraic multiplication and division material in elementary schools. Students do not fully understand the concept of algebraic multiplication and division due to learning obstacles related to limited didactic designs made by teachers. Learning obstacles experienced by students must be anticipated through a learning process that is able to overcome these problems. The researcher developed a didactic learning design using a Realistic Mathematics Education (PMR) approach. The aim of this research is to determine the learning obstacles experienced by students, develop didactical designs for algebraic multiplication and division, describe, test, and describe the designs that have been created. The research method used in this research is Didactical Design Research (DDR). This method consists of three stages, namely didactic situation analysis before learning in the form of Hypothetical Learning Trajectory (HLT) and Pedagogical Didactic Anticipation (ADP), metapedadidactic analysis and retrospective analysis. The data collection technique used is triangulation which combines observation, interviews and documentation. The design development process was carried out in class V with a total of 18 students, and the preliminary study stage was carried out in class IV at SDN 1 Sukamanah with a total of 22 students, and class IV at SDN Sukamulya with a total of 16 students. This research produces data regarding student barriers to multiplication and division material, didactical design in the form of teaching materials, student worksheets (LKPD), to minimize students' learning barriers to multiplication and division material in algebra.